2005
DOI: 10.1186/1471-2164-6-49
|View full text |Cite
|
Sign up to set email alerts
|

How to find soluble proteins: a comprehensive analysis of alpha/beta hydrolases for recombinant expression in E. coli

Abstract: Background: In screening of libraries derived by expression cloning, expression of active proteins in E. coli can be limited by formation of inclusion bodies. In these cases it would be desirable to enrich gene libraries for coding sequences with soluble gene products in E. coli and thus to improve the efficiency of screening. Previously Wilkinson and Harrison showed that solubility can be predicted from amino acid composition (Biotechnology 1991, 9(5):443-448). We have applied this analysis to members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The best expression level was observed when 0.5 OD culture of transformed BL 21 cells was incubated with 1 mm IPTG at 28°C for 3 h. These conditions favoured the most of the expressed protein to be present in soluble fraction in the cell lysate, while at 37°C most of the expressed protein was present as insoluble fraction. Koschorreck et al (2005) have also reported that when (Thomas and Baneyx, 1996;Bragard et al, 2000;Kadkhodayan et al, 2000;Saini and Vrati, 2003), 0.4 mm (Jacob and Usha, 2002) for expression of Cardamom mosaic virus CP and 0.1 mm (Petrzik et al, 2001) for expression of PNRSV CP in E. coli. While in our case, 1 mm IPTG concentration gave the best results.…”
Section: Discussionmentioning
confidence: 98%
“…The best expression level was observed when 0.5 OD culture of transformed BL 21 cells was incubated with 1 mm IPTG at 28°C for 3 h. These conditions favoured the most of the expressed protein to be present in soluble fraction in the cell lysate, while at 37°C most of the expressed protein was present as insoluble fraction. Koschorreck et al (2005) have also reported that when (Thomas and Baneyx, 1996;Bragard et al, 2000;Kadkhodayan et al, 2000;Saini and Vrati, 2003), 0.4 mm (Jacob and Usha, 2002) for expression of Cardamom mosaic virus CP and 0.1 mm (Petrzik et al, 2001) for expression of PNRSV CP in E. coli. While in our case, 1 mm IPTG concentration gave the best results.…”
Section: Discussionmentioning
confidence: 98%
“…Aggregation is difficult to prevent and even to predict on the basis of the amino acid sequence or other protein features, although a few systematic studies have appeared in recent years [9]. Thus, strategies for controlling protein solubility strongly depend on the specific protein and have to be developed case by case with a time-consuming trial and error approach [1,10].…”
Section: Biological and Biotechnological Aspects Of The Aggregation Omentioning
confidence: 99%
“…In a recent study, E. coli cell-free extract was used to screen for well-expressed and highly soluble candidates from a large number of recombinant proteins (11). Recently, computational approaches to predict protein propensity for expression and solubility in an E. coli host have been reported (2,(12)(13)(14)(15)(16). Depending on the expression conditions and nature of the proteins analyzed in these studies, various physicochemical features were implicated as determining factors for an open reading frame (ORF) to yield a soluble expression product in bacteria.…”
mentioning
confidence: 99%